1999
DOI: 10.1021/ma990402v
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Dynamics in Poly(vinylethylene)/Polyisoprene Miscible Blends Revisited. A Neutron Scattering and Broad-Band Dielectric Spectroscopy Investigation

Abstract: Despite the great experimental effort carried out over the past years by means of different techniques, the segmental dynamics in the model blend system poly(vinylethylene)/polyisoprene (PVE/ PI) is still a topic of strong debate. One of the most controversial questions is the possibility of a bimodal distribution of segmental relaxation times for polyisoprene in the blend. In this work, we have combined a microscopic technique, quasielastic neutron scattering (QENS), with molecular isotopic labeling and broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
137
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(146 citation statements)
references
References 31 publications
9
137
0
Order By: Relevance
“…However, Alegria et al [2] found that miscible blends of cis-polyisoprene (PI) and poly(vinyl ethylene) (PVE) exhibit bimodal dielectric loss curves for the local segmental relaxation (a relaxation). Similar dielectric behavior was observed for polymer blends in which the difference of glass transition temperatures T g of the components is larger than 70 K [3][4][5][6][7][8][9][10]. Hereafter the term 'bimodal' means that a loss curve clearly exhibits two peaks or a main peak and a shoulder.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, Alegria et al [2] found that miscible blends of cis-polyisoprene (PI) and poly(vinyl ethylene) (PVE) exhibit bimodal dielectric loss curves for the local segmental relaxation (a relaxation). Similar dielectric behavior was observed for polymer blends in which the difference of glass transition temperatures T g of the components is larger than 70 K [3][4][5][6][7][8][9][10]. Hereafter the term 'bimodal' means that a loss curve clearly exhibits two peaks or a main peak and a shoulder.…”
Section: Introductionsupporting
confidence: 67%
“…Hereafter the term 'bimodal' means that a loss curve clearly exhibits two peaks or a main peak and a shoulder. Dynamic heterogeneity has been investigated by using various methods such as dielectric spectroscopy, [3][4][5][6][7][8][9][10] rheology, [11] and NMR [12][13][14] in which, distinct segmental dynamics of the components were observed as the fast and slow modes. Such a behavior of distinct dynamics has been also known for polymer/diluent systems [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…6 Moreover, a comparison between dielectric and QENS relaxation times can be made since it is well-established that the time scale deduced from neutron scattering at a momentum transfer Q of about 0.9 Å −1 is comparable with that obtained by dielectric spectroscopy. 38,39 As seen in Figure 2 Below 210 K, the relaxation times are fitted by the Arrhenius equation,…”
Section: Resultsmentioning
confidence: 99%
“…Dielectric measurements on such blends reveal significant dielectric loss at high frequency that exhibits weak concentration dependence and is located in a frequency range similar to the response of the neat melt of the lower T g component as illustrated in Figure 13 for a polyisoprene(PI)/poly(vinylethylene) (PVE) blend. 26 For polymer blends such as polystyrene/poly(methyl phenyl siloxane) 27 or polystyrene/poly(vinyl methyl ether), 28,29 where the T g difference between the component polymers is greater than 80 8C, dielectric spectroscopy has clearly showed two distinct relaxations of the fast component where one relaxation was found to have a relaxation time similar to that of the neat melt of the fast component and another closer to that expected based upon blend-average dynamics. Several theoretical models attempt to explain dynamical behavior of blends and their components based on thermally driven concentration fluctuations, 30 chain connectivity, 31 or a combination of both.…”
Section: A-and B-relaxation Processes In Miscible Polymer Blendsmentioning
confidence: 95%